Exploring the suitability and acceptability of peer support for older veterans. (12th June 2017) - Burnell, Karen; Needs, Adrian; Gordon, Kim
Abstract : Purpose: Informal social support is often sought by veterans to support reminiscence or cope with traumatic memories. However, it can also encourage unhelpful ways of coping, such as avoidance, or may be absent altogether. This project is borrowed from the growing peer support literature. The purpose of this paper is to explore the suitability of peer support services to enhance the wellbeing for older veterans, when naturally occurring support is absent or unhelpful. Design/methodology/approach: This was a sequentially staged research programme involving a scoping review of current practice and evidence, and a consultation with veterans. In total, ten veterans (nine male, one female) took part in the consultation ( M =66 years). Findings: Peer support was considered suitable, particularly in addressing loneliness and social isolation. There was an understandable concern regarding its use with more complex issues such as trauma. An added issue was the implicit assumption that this consultation concerned transition; supporting younger veteran as they move from military to civilian life. This mirrored the focus of current UK policy and affected the focus of the consultation. Issues were also raised around the sustainability of services more broadly. Social implications: Peer support is appropriate in supporting older veterans, but must be implemented in a sustainable way. Raising awareness of the needs of older veterans in older adult services is an important implication for service development and delivery. Originality/value: There is a considerable lack of research concerning older veterans, particularly concerning their formal and informal social support needs. This paper addresses the current gap in the literature.